The application of the high seas regime in the exclusive economic zone - Camilleri, Frank-Luke Attard, 1992- (Hamilton Books, 2018)
This book is about the applicability of the high seas regime in the exclusive economic zone (EEZ). It analyses all the relevant provisions of the United Nations Convention on the Law of the Seas (UNCLOS) and goes in depth about the very interesting and complex relationship that exits between the high seas and the EEZ. This book examines three cardinal freedoms of the sea: freedom of navigation, freedom of overflight, and freedom to lay submarine cables and pipelines.--